A case report on decidual cast following B-lynch compression suture - Meena, Laleeta; Budania, Suman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
In case of atonic postpartum haemorrhage (PPH) and traumatic PPH or cervical tear extended deep up to lower uterine segment exploratory laparotomy is the last resort to control PPH. It was a case of 20 years old female admitted in labour room with chief complain of bleeding per vaginum and something coming out of vagina after 6 weeks of post laprotomy for atonic postpartum hemorrhage. Compression sutures were applied and bilateral uterine artery ligation was done at time of laparotomy. After 6 weeks post laparotomy the patient was presented with complain of something coming out from vagina. An examination was performed under short general anesthesia in the operation theater, the mass was removed without any resistance. A provision diagnosis of decidual cast was made which was later confirmed by histopathological report which shows autolytic changes in decidual tissue. Women which are undergoing bilateral uterine artery ligation or compression suture for management of postpartum hemorrhage, should be informed about potential complication. Postoperative follow-up is necessary for any complications.